The hippocampus reevaluated in unconscious learning and memory: at a tipping point? - Hannula, Deborah E.; Greene, Anthony (Frontiers in Human Neuroscience, 2012)
Classic findings from the neuropsychological literature invariably indicated that performances on tests of memory that can be accomplished without conscious awareness were largely spared in amnesia, while those that required conscious retrieval (e.g., via recognition or recall) of information learned in the very same sessions was devastatingly impaired. Based on reports of such dissociations, it was proposed that one of the fundamental distinctions between memory systems is whether or not they support conscious access to remembered content. Only recently have we come to realize that the putative systemic division of labor between conscious and unconscious memory is not so clean. A primary goal of this review is to examine recent evidence that has been advanced against the view that the hippocampus is selectively critical for conscious memory. Along the way, consideration is given to criticisms that have been levied against these findings, potential explanations for differences in the reported results are proposed, and methodological pitfalls in investigations of unconscious memory are discussed. Ultimately, it is concluded that a tipping point has been reached, and that while conscious recollection depends critically on hippocampal integrity, the reach of the hippocampus extends to unconscious aspects of memory performance when relational memory processing and representation are required.